Perancangan Aplikasi Sistem Tata Kelola Rukun Tetangga Menggunakan Pendekatan Design Thinking - Annisa Arumsari; Septian Dwi Cahyo; Tesya Luthfia Rahmah; Asep Taryana (Syntax Corporation Indonesia, 2024)
The emergence of service system problems that are carried out manually which causes inefficiencies that take a long time. The absence of records and data archive management becomes difficult to track finances, decision-making processes and evaluate the overall performance of RTs making a lack of transparency and accountability. The purpose of this research is to design the user interface of the RT administration system application with the design thinking method so as to produce an easy-to-use application user interface as needed as a solution to existing problems. This research uses the design thinking method. The nature of design thinking is human-centered. Design thinking uses strategic innovation to design for users through an empathetic process by trying to understand user needs and focusing on human behavior and emotions to produce optimal innovation. As a result, the creation of the RT administration application user interface utilizes the design thinking method that produces prototypes according to user needs. This prototype became the basis for designing an RT service application with an easy-to-use and intuitive UI. The application of the design thinking method has been proven to help produce an easy-to-use application, which is expected to improve RT services and create a more engaged and informed community of citizens.